Ownership Structure and Firm Value of Quoted Consumers Goods Firms in Nigeria - Godwin Emmanuel Oyedokun; Shehu Isah; Niyi Solomon Awotomilusi (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2020)
This study examined the ownership structure's effect on the firms' value of quoted manufacturing firms (consumer goods) in Nigeria for 2010-2018. The total numbers of quoted consumer goods firms in the Nigeria stock exchange as of 31st December 2018 were twenty-one (21). A judgmental sampling technique was used to sample nineteen (19) consumer goods firms for the study. The study sought to examine whether ownership structure proxy by managerial Ownership, Institutional Ownership, foreign Ownership, and ownership concentration affect firms' values of quoted consumer goods in Nigeria. Data were collected from secondary sources through the annual reports and accounts of sampled consumer goods firms in Nigeria. The study adopted a panel regression technique as a tool of analysis. The result showed a negative effect of managerial ownership on firm value. While institutional Ownership, foreign Ownership, and Ownership concentration all positively affect the firm value of consumer goods firms in Nigeria. Therefore, the study recommends that the numbers of shares held by management should be reduced to increase the firm value of the listed consumer goods companies in Nigeria.